Concurrent Workflow Evolution - Sonntag, Mirko; Karastoyanova, Dimka (Electronic Communications of the EASST, 2011)
Workflow evolution is a collective term for concepts that deal with changes of workflow models. Adapted workflow models are deployed on a workflow engine as new model version. That means two versions of the same model are deployed on the engine. Typically, this results in conflicts between the workflow models. For example, how does a client find and choose the desired workflow version to instantiate? Typically, these problems are solved by deactivating the old model. New instances can only be created for the new model. In our work on scientific workflows we recognized that there are cases where it is desired to keep the old model activated. In this paper we investigate what it means to have several model versions active. We develop a general concept for this “concurrent workflow evolution” that solves emerging problems. Moreover, we show how this concept can be realized with BPEL.